Telaah Epistemologis Kitab Manahil Al-‘Irfan Fi Ulum Al’qur’an Karya Az-Zarqani - Ahsanul Aziz; Halimatussadiyah; Rahmat Hidayat (Indo Publishing, 2026)
This study examines the epistemological critique of the book Manahil al-'Irfan fi Ulum al-Qur'an, written by the prominent scholar Abdul Adzim Az-Zarqani. The formulations and arguments he constructs in the book will be reexamined, developed, and re-evaluated to ensure its value and essence are relevant to social reality. This study uses a library research method. Hopefully, this research will contribute to the advancement of the academic community in particular and be beneficial to its readers.